INTERVENSI PENYEBAB COUNTERPRODUCTIVE WORK BEHAVIOR PADA PENGASUH PANTI ASUHAN XYZ - Riyadi, Astri; Gracious, Levi; Dewanto, Hajar; Savitry S Pandia, Weny; Maysha, Linda (Jurnal Bakti Masyarakat Indonesia, 2024)
XYZ Foundation is an orphanage specifically for children with special needs who need more intensive services than typical children. From the initial meeting with XYZ Orphanage, complaints were made about Counterproductive Work Behavior (CWB) problems in caregivers. CWB itself is defined as a form of dysfunctional behavior and detrimental to both individuals and organizations. CWB that appears to caregivers is that some caregivers seem negligent in doing tasks and lack enthusiasm in working. Caregivers also seem to lack information related to the rules that have been set so that caregivers often violate the rules. In addition, some caregivers are also found to often talk about superiors and there are feelings of mutual dislike which are often caused by misunderstandings between caregivers. In the end, the atmosphere in the caregiver group environment seemed negative so that the caregivers did not help each other, and the caregiver's work was heavy. Poor caregiver performance causes children not to get maximum care and can have an impact on child development. The emergence of counterproductive behavior in XYZ Orphanage is caused by problems in task preparation, job related information, organizational injustice, and less positive group dynamics that have an impact on the emergence of counterproductive work behavior (CWB) in the caregiver group. Thus, interventions are made on these aspects so that XYZ Orphanage caregivers can work more optimally. Interventions made are training and team building to cope with problems in task preparation and group dynamics, also compiled a standard operational procedure of caregiver to solve problem in job related information. Some suggestions also given to help the orphanage manage key performance indicators to cope with organizational injustice. ABSTRAK: Yayasan XYZ merupakan panti asuhan yang dikhususkan untuk anak berkebutuhan khusus yang membutuhkan pelayanan yang lebih intensif dibandingkan anak tipikal. Dari pertemuan awal dengan pihak Panti XYZ, dikeluhkan adanya permasalahan Counterproductive Work Behavior (CWB) yang ada pada pengasuh. CWB sendiri didefinisikan sebagai bentuk perilaku disfungsional dan merugikan baik bagi individu maupun organisasi. CWB yang tampak pada pengasuh adalah beberapa pengasuh tampak lalai dalam mengerjakan tugas dan kurang bersemangat dalam bekerja. Pengasuh juga tampak kurang mengetahui informasi terkait peraturan yang sudah ditetapkan sehingga pengasuh seringkali melanggar peraturan. Selain itu beberapa pengasuh juga didapati sering membicarakan atasan dan adanya perasaan saling tidak suka yang seringkali disebabkan oleh kesalahpahaman antar pengasuh. Pada akhirnya, suasana di lingkungan kelompok pengasuh tampak negatif sehingga pengasuh tidak saling membantu dan pekerjaan pengasuh terasa berat. Performa pengasuh yang kurang baik menyebabkan anak-anak tidak mendapatkan pengasuhan yang maksimal dan dapat berdampak pada perkembangan anak. Timbulnya counterproductive behavior di Panti Asuhan XYZ diakibatkan oleh permasalahan pada task preparation, job related information, adanya organizational injustice, dan dinamika kelompok yang kurang positif sehingga berdampak pada timbulnya perilaku counterproductive work behavior (CWB) pada kelompok pengasuh. Dengan demikian, dilakukan intervensi pada aspek-aspek tersebut agar pengasuh panti asuhan XYZ dapat bekerja lebih optimal. Intervensi yang dilakukan adalah pelatihan dan team building untuk mengatasi masalah dalam task preparation dan dinamika kelompok. Peneliti juga menyusun prosedur operasional standar pengasuh untuk memecahkan masalah dalam job related information. Beberapa saran juga diberikan untuk membantu panti asuhan mengelola indikator kinerja utama untuk mengatasi organizational injustice.